2016
DOI: 10.1016/j.applanim.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of odour, taste and nutrients on feeding behaviour and food preferences in horses

Abstract: Highlights (for review):-The effect of odour, taste and nutrients on diet intake by horses was examined.-Two-choice and multiple-choice tests were used to evaluate feeding behaviour.-Nutrient content appeared to be the main driver for diet choices.-Taste appeared secondary to nutrients in determining the diet selected.-The multiple-choice test was able to more clearly differentiate in diet ranking. AbstractWhile it has been established that nutrients and flavours (odour, taste) play an important role in diet s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…In the study by van den Berg et al ( 2016) nutrient content was mentioned as the most important criterion for food rejection in horses followed by the food's taste. Odour had the lowest effect on food intake [21]. In another study, van den Berg et al ( 2016) stated that a well-known non-nutritive odour like fresh lucerne reduced the neophobic effect in horses when lucerne odour was added to a novel food [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by van den Berg et al ( 2016) nutrient content was mentioned as the most important criterion for food rejection in horses followed by the food's taste. Odour had the lowest effect on food intake [21]. In another study, van den Berg et al ( 2016) stated that a well-known non-nutritive odour like fresh lucerne reduced the neophobic effect in horses when lucerne odour was added to a novel food [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the findings of the studies previously mentioned demonstrated that horses had a greater preference for familiar diets and that horses showed a strong neophobic response towards unfamiliar diets. A discrimination based on macronutrient content required an adaptation period for at least three meals [21,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In our trials, ponies tended to sample from both hay alternatives (flavoured and water) and to select an equal proportion of feed from both buckets, whenever new flavours were accepted. As reported by Van den Berg (2016a, 2016b, 2016d horses display patch foraging behavior sampling from all foods offered and an equal proportion of familiar and new feed eaten during multiple choice test (van den Berg et al, 2016d). The same authors showed also a similarity for the time spent walking towards different "forage zones".…”
Section: Palatability Testsmentioning
confidence: 61%
“…Beside palatability or stimulating odour, adaptation periods to feedstuff seemed to be important in selection behaviour of horses. Several studies showed that horses preferred feeds with high content of proteins, carbohydrates (starch and sugar) or energy levels if they were adapted to these diets for at least three to five days or 10 feeding sessions (Cairns et al, 2002; Redgate et al, 2014; Van den Berg, Giagos, Lee, Brown, Cawdell‐Smith, et al, 2016). However, in our study, the intake of MS was mainly observed at the beginning of the experiment within the first two observation periods.…”
Section: Discussionmentioning
confidence: 99%